2008
DOI: 10.1016/j.ode.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

ITS2 secondary structure and phylogeny of cyst-forming nematodes of the genus Heterodera (Tylenchida: Heteroderidae)

Abstract: The internal transcribed spacer 2 (ITS2) of the ribosomal RNA gene is a double-edged tool for eukaryote evolutionary comparison. In this paper, we re-evaluate the putative ITS2 secondary structures proposed for 29 species of cyst-forming nematodes in the genus Heterodera and present optimized variants. The models are organized in four main helices emerging from a central core. Helix III is always the longest and has two branches exhibited as a Y-shaped structure near the apex. In most species, helices III and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Slight differences in structures proposed in our study from those by Marek et al (2010) can be explained by the different methods and folding parameters used and may also reflect the dynamic nature of the ITS2 structure flexing between alternative folding patterns (Ma et al, 2008). The ITS1 transcript of D. destructor proposed in our study represents three domain structures.…”
Section: Discussionmentioning
confidence: 55%
“…Slight differences in structures proposed in our study from those by Marek et al (2010) can be explained by the different methods and folding parameters used and may also reflect the dynamic nature of the ITS2 structure flexing between alternative folding patterns (Ma et al, 2008). The ITS1 transcript of D. destructor proposed in our study represents three domain structures.…”
Section: Discussionmentioning
confidence: 55%
“…Several recent studies have proved that ITS2 molecular morphometric analysis could be effectively used to resolve eukaryotic organisms at the genus and species level. Ma et al [33] reported that the application of secondary structure information provides a realistic picture of relationships within Heterodera . Chen et al [100] and Han et al [34] demonstrated the potential use of the ITS2 region as a standard DNA barcode to identify medicinal plants and their closely related species.…”
Section: Discussionmentioning
confidence: 99%
“…We followed the 28-symbol method of Subbotin [ 27 , 38 ] and considered each of the four bases in helixes as six states (e.g., AA, AC, AG, AU, A-,-A), together with each of the four base states in loops as additional symbols [ 27 ]. After each state was designated as separate character a new structure information matrix was produced through RNAstat software [ 27 ].…”
Section: Methodsmentioning
confidence: 99%